Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1097/01.aud.0000188116.30954.21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Clarion CII HiFocus 1 with and Without Positioner

Abstract: A basally perimodiolar electrode design benefits speech perception. The combination of decreased distance to the modiolus, improved insertion depth, and insulating properties of the electrode array have functional implications for the clinical outcomes of the perimodiolar electrode design. Further research is needed to elucidate their individual contributions to those outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 43 publications
2
40
1
4
Order By: Relevance
“…Electrode field potential can be obtained by stimulating one electrode while recording the potential in other non-stimulating electrodes. Electrical field imaging plots the potential distribution as a function of electrode position and can be a useful clinical tool to probe the interference and interaction between electrodes [108].…”
Section: Back Telemetrymentioning
confidence: 99%
“…Electrode field potential can be obtained by stimulating one electrode while recording the potential in other non-stimulating electrodes. Electrical field imaging plots the potential distribution as a function of electrode position and can be a useful clinical tool to probe the interference and interaction between electrodes [108].…”
Section: Back Telemetrymentioning
confidence: 99%
“…Factors affecting this interface include the distance to the modiolus, the amount and density of excitable nerve fibers, the amount of fluid surrounding the electrode and the presence of scar tissue. Several studies have shown that the intracochlear electrode position is correlated with speech perception scores [Finley et al, 2008;Holden et al, 2013;van der Beek et al, 2005]. The relationship between the intracochlear electrode position and the outcomes of cochlear implantation appears to be a reflection of the efficacy of the transfer of the electrical stimulus to the nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Close proximity to the modiolus has been shown to lower M levels or C levels (depending on the brand) and electrically evoked compound action potential thresholds, which facilitate more focused stimulation and optimization of pulse width [Dorman et al, 2007;Filipo et al, 2008;van der Beek et al, 2005;van Wermeskerken et al, 2009]. According to Briggs et al [2001], proximity to the modiolus can be achieved without intracochlear damage, provided a free-fitting electrode array of appropriate size and shape is used and inserted in the scala tympani.…”
Section: Introductionmentioning
confidence: 99%
“…The relation between electrode position and speech perception is an often studied one [Aschendorff et al, 2007;Baskent and Shannon, 2005;Finley et al, 2008;Skinner et al, 2007;van der Beek et al, 2005;Yukawa et al, 2004]. Frequency alignment, the prevention of intracochlear trauma and the preservation of residual hearing are important topics related to this matter.…”
Section: Introductionmentioning
confidence: 99%